Elite and non-elite translator manpower: The non-professionalised culture in the translation field in Israel - Rakefet Sela-Sheffy (JoSTrans: The Journal of Specialised Translation)
In occupational fields, centre-periphery relations are contingent on a process of professionalisation, which is a symptom of status struggles, with expert elites claiming privileges by monopolising knowledge and skills. In the translatorial occupations, despite recently increasing efforts toward professionalisation, this process still seems to be suspended, with elite literary translators cultivating a counter-professionalisation ethos to secure their status. Taking the situation in Israel as an extreme example, I use findings from a first comprehensive interview-based study of its kind in Israel to discuss the permeation of a counter-professionalisation trend in the field of translatorial occupations at large. I examine the effect of an anti-professionalisation ethos on the self-perception of non-elite practitioners in the different branches of this occupation (commercial and technical translators, non-elite literary translators, subtitlers, conference and community interpreters). I argue that this ethos, with its artisation-oriented nature, determines the prestige scale in this occupational field, and thus has crucial impact on shaping the relations between elite and non-elite manpower in it. While top literary translators draw on it for their sense of distinction and privileges, for the largest population of non-elite translators, lacking a sense of personal agency and cultural role, this ethos serves as a buffer to capitalising on alternative resources that are usually attached to professionalism.